2006
DOI: 10.1590/s1516-35982006000500019
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de extratos vegetais e antimicrobianos sobre a digestibilidade aparente, o desempenho, a morfometria dos órgãos e a histologia intestinal de leitões recém-desmamados

Abstract: RESUMO -Objetivou-se com este trabalho avaliar o efeito de antimicrobianos e extratos vegetais sobre a digestibilidade, o desempenho, a morfometria e a histologia de leitões recém-desmamados. Foram realizados três experimentos de 35 dias (repetições no tempo), com um total de 120 leitões (40 leitões por experimento). O delineamento foi em blocos casualizados, com cinco tratamentos (controle -ração basal; antimicrobiano -ração basal com bacitracina de zinco, olaquindox e colistina (50 ppm de cada); extrato vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
34

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 13 publications
4
22
0
34
Order By: Relevance
“…Lee et al (2003) observed an increase of intestinal amylase activity in chickens at 21 days of age receiving a combination of plant extracts in the diet, and trypsin at 46 days of age, concluding that the sensitivity of the endogenous enzymes can be modified by the plant extracts according to the age of the animal. This could explain the results obtained by Oetting et al (2006), who observed an increase in dry matter digestibility when testing herbal extract consisting of essential oil of clove, thyme and oregano, added to the active ingredients eugenol and carvacrol. This diet was compared to the control diet or one containing a combination of antimicrobials (olaquindox, colistin and bacitracin).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Lee et al (2003) observed an increase of intestinal amylase activity in chickens at 21 days of age receiving a combination of plant extracts in the diet, and trypsin at 46 days of age, concluding that the sensitivity of the endogenous enzymes can be modified by the plant extracts according to the age of the animal. This could explain the results obtained by Oetting et al (2006), who observed an increase in dry matter digestibility when testing herbal extract consisting of essential oil of clove, thyme and oregano, added to the active ingredients eugenol and carvacrol. This diet was compared to the control diet or one containing a combination of antimicrobials (olaquindox, colistin and bacitracin).…”
Section: Resultsmentioning
confidence: 62%
“…Wang & Bourne (1998) proposed that some herbal extracts can also stimulate the pancreatic secretion, which is linked to the improvement of nutrient digestibility. Lewis et al (2004) and Oetting et al (2006) founded no significant numerical increase of pancreas weight when using the herbal extracts. Lee et al (2003) observed an increase of intestinal amylase activity in chickens at 21 days of age receiving a combination of plant extracts in the diet, and trypsin at 46 days of age, concluding that the sensitivity of the endogenous enzymes can be modified by the plant extracts according to the age of the animal.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Apesar de não ocorrerem diferenças estatísticas (P>0,05) entre os tratamentos, o maior peso relativo do pâncreas foi constatado no tratamento controle negativo, o qual também apresentou um maior valor numérico para concentração de amilase (Quadro 3). Dados da literatura sugerem que o aumento do pâncreas pode estar relacionado a um maior estímulo na secreção pancreática e ao aumento da atividade enzimática promovido pela adição de extratos vegetal (Oetting et al 2006), entretanto não foram observadas diferenças significativas no presente estudo.…”
Section: Quadro 2 Descrição Dos Tratamentos De Acordo Com a Porção Vunclassified
“…No entanto, com a proibição desses aditivos na produção animal (BRUGALLI, 2003), houve estímulo para a busca de alternativas aos antibióticos promotores de crescimento por agentes não menos efetivos, mas reconhecidos como seguros (MENTEN, 2001), como os extratos vegetais, óleos essenciais, prebióticos e probióticos (SILVA et al, 2011 Os fi toquímicos tornaram-se uma opção aos antibióticos, porque melhoram a digestibilidade dos alimentos, pois estimulam a produção de enzimas digestivas e de secreções entéricas, alterações na microbiota intestinal e propiciam modifi cações morfohistológicas do trato gastrointestinal (ZANINI et al, 2006;JAMROZ et al, 2006;OETTING et al, 2006;SILVA et al, 2010).…”
Section: Introductionunclassified